Microvesicles expressing adenosinergic ectoenzymes and their potential role in modulating bone marrow infiltration by neuroblastoma cells. (4th May 2019) - Morandi, Fabio; Marimpietri, Danilo; Horenstein, Alberto L.; Corrias, Maria Valeria; Malavasi, Fabio
ABSTRACT: Metastatic diffusion of Neuroblastoma (NB) cells in the bone marrow (BM) represents the most negative prognostic factors for NB patients. Multiple immune escape mechanisms are postulated as responsible. Our working hypothesis is that adenosine (ADO), an immunosuppressive molecule along with the ectoenzymatic pathways (CD39-CD73 and CD38-CD203a/PC-1-CD73) controlling its production, are involved in the dynamics of NB cells in the BM. The results indicate that ectonucleotidases are expressed by i) NB cell lines, ii) metastatic NB cells isolated from NB patients' BM, iii) microvesicles (MV) derived from both NB cell types and iv) resident BM cell populations. BM infiltration by NB cells increased CD203a/PC-1 and CD73 expression on lymphoid and myeloid cells, respectively. Expressions of ectoenzymes and GD2 (NB-associated marker) were higher on MV from NB patients' BM than in controls. Moreover, CD203a/PC-1 expression on BM-derived MV provide a basis for distinguishing NB patients with high or low BM infiltration. ADO production and consumption of related by-products were significantly higher when assessed on NB patients' MV than those from controls. MV isolated from NB patients' BM significantly downregulated in vitro T cell proliferation. Lastly, NB patients with worse prognosis are identified by a high percentage of CD38 + or CD73 + MV in the BM. In conclusion, ectonucleotidases are present and functional on NB cells, as well as in NB-infiltrated BM and in MV derived from BM. It is reasonable that MV are involved in BM infiltration by NB cells. Therefore, targeting these molecules may widen the therapeutic armamentarium for metastatic NB patients.